Growth in individuals with Saul–Wilson syndrome. Issue 9 (11th July 2020) - Ferreira, Carlos R.; Niiler, Timothy; Duker, Angela L.; Jackson, Andrew P.; Bober, Michael B.
Abstract: Saul–Wilson syndrome (SWS) is a rare autosomal recessive disorder characterized by microcephalic primordial dwarfism, spondyloepimetaphyseal dysplasia, characteristic facial findings, clubfoot, brachydactyly, bilateral cataracts, and hearing loss. Recently, recurrent mutations in COG4, encoding a component of the Conserved Oligomeric Golgi (COG) complex, were identified. We created detailed growth curves for stature, weight, and head circumference, as well as weight‐for‐length and weight velocity charts for younger children, derived from hundreds of data points obtained by retrospective chart review from 14 individuals with molecularly‐confirmed SWS. In addition, we performed statistical comparisons of height‐for‐age model fits before and after initiation of growth hormone supplementation, and found that this therapy does not appear to influence height in individuals with SWS. We hope that these charts will represent valuable tools for clinicians, both in assessing whether SWS seems an appropriate diagnosis, as well as to monitor growth of affected individuals. In particular, we hope that our detailed growth characterization will reduce morbidity resulting from unnecessarily aggressive nutritional interventions by well‐intentioned physicians trying to promote weight gain, an unrealistic goal in this genetically‐determined cause of primordial dwarfism.